3.
Упростим 1 уравнение сиистемы:
15+2х+6у=12х+3у
-10х+3у=-15
Упростим 2 уравнение:
10х-2у-3у=2+6х-3у
4х-2у=2
Соединяем в систему:
-10х+3у=-15
4х-2у=2
-10х+3у=-15
4х=2(1+у)
-10х+3у=-15
2х=1+у
-10х+3у=-15
у=2х-1
-10х+3(2х-1)=-15
у=2х-1
-10х+6х-3=-15
у=2х-1
х=3
у=5
4.
Упрощаем 1 уравнение:
35х+10у-11у=12х+6у+2
23х-7у=2
23х=2+7у
х=(2+7у)/23
Упрощаем 2 уравнение:
33+18х-15у=3х+6у-5у
15х-16у=-33
Подставляем в систему:
х=(2+7у)/23
15х-16у=-33
х=(2+7у)/23
15(2+7у)/23-16у=-33
х=(2+7у)/23
у=3
х=(2+7*3)/23
у=3
х=1
у=3
След.страница.
№3(№4-НЕ ВИДЕН!)
Упрощаем 1 уравнение:
(3у+х)/ху=13/ху
3у+х=13
х=13-3у
Упрощаем 2 уравнение:
(8у-2х)/ху=16/ху
8у-2х=16
Соединяем в систему:
х=13-3у
8у-2х=16
х=13-3у
8у-2(13-3у)=16
х=13-3у
у=3
х=13-3*3
у=3
х=4
у=3